Inflammatory Mediator Profiling Reveals Immune Properties of Chemotactic Gradients and Macrophage Mediator Production Inhibition during Thioglycollate Elicited Peritoneal Inflammation. (31st March 2013) - Lam, Derek; Harris, Devon; Qin, Zhenyu
Abstract : Understanding of spatiotemporal profiling of inflammatory mediators and their associations with MΦ accumulation is crucial to elucidate the complex immune properties. Here, we used murine thioglycollate elicited peritonitis to determine concentrations of 23 inflammatory mediators in peritoneal exudates and plasma before (day 0) and after (days 1 and 3) thioglycollate administration to peritoneal cavities; these mediators included TNF- α, FGF-9, IFN- γ, IP-10, RANTES, IL-1 α, IL-6, IL-7, IL-10, IL-11, IL-12p70, IL-17A, lymphotactin, OSM, KC/GRO, SCF, MIP-1 β, MIP-2, TIMP-1, VEGF-A, MCP-1, MCP-3, and MCP-5. Our results showed that concentrations of most mediators in exudates and plasma reached peak levels on day 1 and were significantly reduced on day 3. Conversely, MΦ numbers started to increase on day 1 and reached peak levels on day 3. Moreover, LPS treatment in vitro significantly induced mediator productions in cell culture media and lysates from MΦ isolated on day 3. Our results also showed that on day 0, concentrations of many mediators in plasma were higher than those in exudates, whereas on day 1, the trend was reversed. Overall, the findings from thioglycollate elicited peritonitis reveal that reversible chemotactic gradients between peritoneal exudates and blood exist in basal and inflamed conditions and the inflammatory mediator production in vivo is disassociated with macrophage accumulation during inflammation resolution.